Phase investigation of an iron meteorite from Akyumak - Aksoy, I; Ceylan, M; Kayali, N (Elsevier Science Sa Lausanne, 1996)
The phase of an iron meteorite which fell near Akylumak, East Anatolia, in 1981 have been investigated by optical and X-ray diffraction. Diffraction peaks of kamacite, teanite, plessite and cementite phases were separated and indexed by the related unit cell parameters of the phases. From the analysis of DSC and DTA curves, some phase transformation are known to have occurred during different heating regimes.